Faktor Penghambat Pelaksanaan Bimbingan Konseling Kelompok di SMP PAB 10 Medan Estate - Harahap, Ade Chita Putri; Surbakti, Fitri Br; Linri, Linri; Miranda, Miranda; Nadila, Olga Rizki; Lubis, Septi Aulia; Siregar, Sri Intan (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
Group guidance and counseling is one of the important services in schools. However, at SMP PAB 10 Medan Estate, the implementation of group guidance and counseling has encountered several obstacles. The aim of this study is to identify and analyze inhibiting factors that affect the implementation of group guidance and counseling at SMP PAB 10 Medan Estate. This study uses a qualitative approach with data collection techniques through interviews and observations. The results of the study show that there are several inhibiting factors that affect the implementation of group guidance and counseling at SMP PAB 10 Medan Estate, including lack of support from the school, lack of knowledge and skills of the BK teacher, as well as lack of participation and motivation of students.